Development of Interactive Multimedia Based on Problem Based Learning and Liveworksheets to Improve IPAS Learning Outcomes - Salsabila, Salsabila; Andriani , Aldina Eka (Journal of Educational Sciences, 2025)
Teachers have not yet fully utilized technology-based media and innovative learning approaches, which has contributed to low student achievement. This study aimed to develop, validate, and evaluate the effectiveness of interactive multimedia designed with a Problem-Based Learning approach and enhanced by Liveworksheets to improve fifth-grade students’ IPAS learning outcomes. The research applied a Research and Development (R&D) method using the ADDIE model as the framework. The participants were 21 fifth-grade students from State Elementary School (SDN) 1 Bawu Jepara. Data were collected through tests and non-test techniques, including observation, interviews, questionnaires, and documentation. The findings revealed that: (1) the developed multimedia included a main menu, user guide, learning materials, games, Liveworksheets-based assessments, and references; (2) its feasibility was rated very high by experts, teachers, and students; and (3) the product was proven effective in improving students’ engagement and learning outcomes. Therefore, the interactive multimedia developed in this study is both feasible and effective as a tool to enhance IPAS learning for elementary school students.